APLIKASI PENGELOLAAN KEUANGAN PADA PERGURUAN ADVENT SIMBOLON - Ika Putri Hutajulu; Marlyna Infryanty Hutapea; Dimita Hemalli Premasari Purba (Universitas Methodist Indonesia, 2019)
The Simbolon Adventist College is one of the private status schools in the area of ​​Samosir, Palipi District. This school has used computer equipment in carrying out its work activities, such as Microsoft Office Excel. However, the use of computer devices only utilizes small activities such as calculating cash income and expenditure and making reports. Administration of data processing that is processed by the finance department is still manual, namely in the form of files. The administrative data processing in question, such as recording the cash in the school as well as the cash out used by the parties, as if they were still using the records in the books stored in the storage cabinet. The problems found are data redundancy, file buildup will cause the file to be damaged, and require a long time to search for information because of the large number of files. Making Simbolon Adventist College Information System using Microsoft Visual Studio 2010 programming language, Microsoft Office Access 2007, and Crystal Report 8.5. The results of making the system are optimal computer use and simplify the financial management of the Simbolon Adventist College and assist in the process of inputting school financial data and presentation of reports.